Teaching, Learning, and Employing Analytical Frameworks as Performance: Analysis of a Quantitative Literacy Event in Applied Mechanics - Zach Simpson; Robert Prince (Stockholm University Press, 2018)
Quantitative literacy is the ability to solve problems using mathematical and statistical information that is represented in various forms, including visual, written and mathematical forms. It is central to many of the disciplines within higher education. In this paper, we examine a particular quantitative literacy event within an undergraduate applied mechanics module and, in so doing, argue that teaching and learning are cultural performances of individuals' relations to, in this case, quantitative literacy. Furthermore, we apply a framework for analysing the quantitative literacy demands present within higher education. By applying this framework in a critically reflexive manner, we demonstrate how the researcher similarly engages in a cultural performance in relation to quantitative literacy. We use this anecdotal example to argue that the application of analytical frameworks is inherently performative in nature, and propose the need for a meta-frame for understanding teaching, learning, and the frameworks through which they are viewed, as performance. This has implications for higher education more broadly in that, we argue, the frameworks used promote particular relations to lived teaching and learning experiences, and position teachers, learners, researchers and curriculum developers in particular ways.